A mild copper-catalyzed aerobic oxidative thiocyanation of arylboronic acids with TMSNCS. Issue 3 (27th November 2014) - Sun, Nan; Che, Liusheng; Mo, Weimin; Hu, Baoxiang; Shen, Zhenlu; Hu, Xinquan
Abstract : A facile and generalized synthesis of aryl thiocyanates has been established via the CuCl-catalyzed oxidative coupling of arylboronic acids with TMSNCS. The reaction could be conducted at RT and under an O2 atmosphere. Abstract : A facile and efficient transformation of arylboronic acids to their corresponding aryl thiocyanates has been successfully developed. Based on the CuCl-catalyzed oxidative cross-coupling reaction between arylboronic acids and trimethylsilylisothiocyanate (TMSNCS) under oxygen atmosphere, the transformation can be readily conducted at ambient temperature. The newly-developed protocol provided a competitive synthetic approach to aryl thiocyanates that can tolerate a broad range of reactive functional groups and/or strong electron-withdrawing groups.